Micro-Nano Mechatronics New Trends in Material, Measurement, Control, Manufacturing and Their Applications in Biomedical Engineering - Fukuda, Toshio; Niimi, Tomohide; Obinata, Goro (IntechOpen, 2013)
Micro/Nano mechatronics is currently used in broader spectra, ranging from basic applications in robotics, actuators, sensors, semiconductors, automobiles, and machine tools. As a strategic technology highlighting the 21st century, this technology is extended to new applications in bio-medical systems and life science, construction machines, and aerospace equipment, welfare/human life engineering, and other brand new scopes. Basically, the miniaturizing technology is important to realize high performance, low energy consumption, low cost performance, small space instrumentation, light-weight, and so on. This book presents the summary of our project Center of Excellence for Education and Research of Micro-Nano Mechatronics. The project implements a strategy to realize applications of micro-nano mechatronics, which are based on mechanical engineering or materials science, control systems engineering, and advanced medical engineering. The chapters describe the research advances in micro/nano measurement and control, micro/nano design and manufacturing, nano materials science, and their applications in biomedical engineering. The publication of this book was supported by Nagoya University, the 21st COE program "Micro- and NanoMechatronics for Information-Based Society," and the global COE program "COE for Education and Research of Micro-Nano Mechatronics."